Altered gut microbiota in patients with small intestinal bacterial overgrowth. Issue 1 (19th October 2022) - Bamba, Shigeki; Imai, Takayuki; Sasaki, Masaya; Ohno, Masashi; Yoshida, Shinya; Nishida, Atsushi; Takahashi, Kenichiro; Inatomi, Osamu; Andoh, Akira
Abstract: Background and Aim: Small intestinal bacterial overgrowth (SIBO) is diagnosed by using quantitative culture of duodenal aspirates and/or a hydrogen breath test. However, few studies have analyzed bacterial microbiota in Japanese patients with SIBO. Methods: Twenty‐four patients with any abdominal symptoms and suspected SIBO were enrolled. Quantitative culture of duodenal aspirates and a glucose hydrogen breath test were performed on the same day. SIBO was diagnosed based on a bacterial count ≥ 10 3 CFU/mL or a rise in the hydrogen breath level of ≥ 20 ppm. The composition of the duodenal microbiota was analyzed by 16S rRNA gene sequencing. Results: Small intestinal bacterial overgrowth was diagnosed in 17 of the 24 patients (71%). The positive rates for the hydrogen breath test and quantitative culture of duodenal aspirates were 50% and 62%, respectively. Patients with SIBO showed significantly reduced α‐diversity compared with non‐SIBO patients, and analysis of β‐diversity revealed significantly different distributions between SIBO and non‐SIBO patients. In addition, the intestinal microbiome in SIBO patients was characterized by increased relative abundance of Streptococcus and decreased relative abundance of Bacteroides compared with non‐SIBO patients. Conclusions: Duodenal dysbiosis was identified in patients with SIBO and may play a role in the pathophysiology of SIBO.